2022
DOI: 10.1021/acs.cgd.2c00849
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-Level Investigation of Hydrate–Anhydrous Phase Transformations of the Dapsone Structurally Related Compound 3,3′-Diaminophenyl Sulfone

Abstract: The solid state of a novel hydrate form of 3,3′diaminophenyl sulfone (3APS_0.5H 2 Oo) as well as its temperatureinduced phase transitions is reported. On increasing the temperature, first a partial dehydration occurs, leading to the partially hydrated 3APS_0.1H 2 Oo, which then transforms into the monoclinic anhydrous form, 3APS_Am. Finally, by recrystallization of the melt 3APS_Am, a second anhydrous orthorhombic phase is obtained (3APS_Ao). This last phase transforms in 3APS_Am at a temperature between 360 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…Choosing the most appropriate resolving agent can be tricky and time-consuming so that it is often widely empirical. X-ray diffraction, along with various thermoanalytical techniques and in silico approaches, serves as an essential tool for exploring the forces and interactions in crystal packing, hence playing a crucial role in understanding the driving forces behind the formation of structurally related diastereomeric salts. …”
Section: Introductionmentioning
confidence: 99%
“…Choosing the most appropriate resolving agent can be tricky and time-consuming so that it is often widely empirical. X-ray diffraction, along with various thermoanalytical techniques and in silico approaches, serves as an essential tool for exploring the forces and interactions in crystal packing, hence playing a crucial role in understanding the driving forces behind the formation of structurally related diastereomeric salts. …”
Section: Introductionmentioning
confidence: 99%
“…For example, 3,3′-diaminophenyl sulfone (3APS) was shown to form hemihydrate (3APS_0.5H 2 O), which was transformed into anhydrate (3APS_A), upon heating, via the formation of an intermediate phase (3APS_0.1H 2 O). 24 Recently, we have shown that the as-synthesized 1,4-bis(4,5diphenyl-1H-imidazol-2-yl)benzene (BDPI) exists as a tetrahydrate for which the single crystals cannot be obtained. 25 However, the crystal structure was determined by its powder diffraction.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The dehydration process can also occur in a stepwise manner with the formation of one/multiple intermediate hydrate phases, but identification of such intermediate phases is very difficult due to the lack of stability. For example, 3,3′-diaminophenyl sulfone (3APS) was shown to form hemihydrate (3APS_0.5H 2 O), which was transformed into anhydrate (3APS_A), upon heating, via the formation of an intermediate phase (3APS_0.1H 2 O) …”
Section: Introductionmentioning
confidence: 99%